PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PD. BPR BANK KLATEN DENGAN KOMITMEN ORGANISASI SEBAGAI INTERVENING - Kesdu, Purwito (AKTUAL, 2014)
The purpose of this study is to determine the influence of leadership and motivation on employees performance at PD. BPR Bank Klaten with an organizational commitment as an intervening variable. The result shows that : there is the influence of leadership, motivation, and organizational commitment as a variable intervening on employees performance at PD BPR Bank Klaten. This study is a survey to PD. BPR Bank employees Klaten with 70 employees as the sample . Data have been collected by questionnaires processed by a linier regression, path analysis, t test, F test and test R2. T tests shows that there is an influence of leadership, motivation, and organizational commitment to employees performance at PD BPR Bank Klaten. The F tests has shown that there is an influence of leadership, motivation, and organizational commitment to employees performance at PD. BPR Bank Klaten simultaneously. The path analysis showed that leadership has a greater influence on the performance of the entire variables: organization commitment and the motivation too. This means that organizational commitment canât be as an intervening variable, it is as small as the coefficient of a direct influence. From R2 test shows the performance of the independent variables can explain about 87% and 13% can be explained by other variables: communication, ability and work discipline. Keyword: leadership, motivation, organization commitment and performance